Endovascular repair of subclavian artery injury secondary to internal jugular vein catheterization: case report - Kim,Jong Ho (2019)
Abstract Background and objectives Ultrasound-guided internal jugular vein catheterization is a common and generally safe procedure in the operating room. However, inadvertent puncture of a noncompressible artery such as the subclavian artery, though rare, may be associated with life-threatening sequelae, including hemomediastinum, hemothorax, and pseudoaneurysm. Case report We describe a case of the successful endovascular repair of right subclavian artery injury in a 75-year-old woman. Subclavian artery was injured secondary to ultrasound-guided right internal jugular vein catheterization under general anesthesia for orthopedic surgery. Conclusion Under general anesthesia several factors such as hypotension can mask the signs of subclavian artery injury. This case report indicates that clinicians should be aware of the complications of central venous catheterization and take prompt action.